Role of the promoter in the regulation of the thymidine kinase gene. - Travali, S (1988)
To identify the regulatory elements of the human thymidine kinase (TK) gene, we have established stable cell lines carrying different chimeric constructs of the TK gene. Our results can be summarized as follows. (i) When the TK coding sequence is under the control of the calcyclin promoter (a promoter that is activated when G0 cells are stimulated by growth factors), TK mRNA levels are higher in G1-arrested cells than in proliferating cells; (ii) when the TK coding sequence is under the control of the promoter of heat shock protein HSP70, steady-state levels of TK mRNA are highest after heat shock, regardless of the position of the cells in the cell cycle; (iii) the bacterial CAT gene under the control of the human TK promoter is maximally expressed in the S phase; (iv) the TK cDNA driven by the simian virus 40 promoter is also maximally expressed in the S phase; and (v) TK enzyme activity is always at a maximum in the S phase, even when the levels of TK mRNA are highest in nonproliferating cells. We conclude that although the TK coding sequence may also play some role, the TK promoter has an important role in the cell cycle regulation of TK mRNA levels.